Abducted Ground: The Ineffaceable Beaduric’s Island’ - Murray, Shaun (Architecture Image Studies, 2020)
To occupy is to reside, take up space of time, be situated within or hold a position. To keep yourself busy or distracted (by doing something). To ‘seize’ other words engage, involve, engross, preoccupy, divert, immerse. To occupy drawing in architecture has a vast unwritten history. From Frederick Kiesler’s ‘Correalism’ (Kiesler, 1939) in the 1930s up to the publication of ‘Reflexive Architecture’ in Architectural Design (Spiller, 2002) in the 2000s architects have adducted the drawing and occupied it to investigate fresh ideas of speculative practices as investigations and innovations.